Moringa oleifera extract affects the diameter of the Graafian follicles in female Mus musculus - Amiruddin; Herman, Sriyana; Balumbi, Musthamin; Rahawarat, Marwia; Darlian, Lili; Fitrianingsih, Julia; Handayani, Rika; Rusli (Universitas Airlangga, 2024)
HIGHLIGHTS This study unveils a dose-dependent relationship between Moringa leaf extract and increased Graafian follicle size in female mice. The significant positive effect of Moringa leaf extract on Graafian follicles suggests promising implications for fertility interventions, offering hope for individuals seeking natural treatment to address infertility challenges. ABSTRACT Objective: This study aimed to determine the effect of Moringa leaf extract (Moringa oleifera Lam.) on the diameter of Graafian follicles in female mice (Mus musculus). Materials and Methods: This study used experimental design, employing a cohort of 24 female mice of 20-25 grams in weight, aged between 2-3 months, and in good health. These subjects were divided into three treatment groups and subjected to oral doses of Moringa leaf extract at 300 mg/kg BW, 400 mg/kg BW, and 500 mg/kg BW over a 14-day period. The study procedures involved the preparation of the experimental animals, preparation of Moringa leaf extract, treatments administration, and the preparation of histological specimens. Subsequently, the diameters of Graafian follicles within each treatment group were measured. Data analysis were performed using the ANOVA test (p <0.05) followed with the Least Significance Difference (LSD) test utilizing the IBM SPSS software. Results: There were variations in Graafian follicle diameters across the experimental groups. The average diameters were 180.944 µm in the control group, 239.942 µm in treatment group 1, 315.006 µm in treatment group 2, and 396.650 µm in treatment group 3. This indicated that dose administration starting from 300 mg/kg, 400 mg/kg, and 500 mg/kg had an effect on the size of the follicle and antrum diameter. The number of granulosa cells was found to increase, as well as the size of the ovum. Conclusion: Moringa leaf extract in different doses has a significant positive effect on increasing the diameter of the Graafian follicles in female mice.